(untitled) (The Journal of Medicine, Humanity and Media, 2025)
On July 10, 2025, the South China University of Technology session of the 8th International Conference on “Medicine, Humanity, and Media” (MHM2025) was held at Peking University’s School of Journalism and Communication. Led by Professor Rui Jian, the forum focused on “Intelligent Empowerment and Humanistic Integration: AI in Health Communication—Innovations and Audience Insights.” Five scholars presented their latest studies. Topics included the role of social support in AI health communication, the effects of chatbot communication styles on persuasion, predictors of older adults’ technology adoption, the persuasive limits of AI-generated health content, and media portrayals of AI-assisted medicine. Employing methods such as experiments, systematic analysis, and surveys, these studies revealed that evaluation support enhances self-efficacy more effectively.